PEMBUATAN ALAT UJI RUGI-RUGIALIRAN DALAM PIPA SIRKULASI TERTUTUP DENGAN KEMIRINGAN 30 0 - Dedi Wardianto (Menara Ilmu, 2016)
Pratikum basic phenomena machinery required for S1 Mechanical Engineering, as a means toimprove the understanding of learning (psychomotor) on students. then try to make this finalanalysis tool flow losses in the circulation pipe covered with a slope of 30 0. To obtain avariation of the flow supplied pipe 1 inch, ¾ inch, ½ inch, 5/8 inch and valves with variousopenings. FWP 225 by using a pump capacity of 75 liters / min maximum pressure obtained 9kgf / cm², with a pressure gauge 4 kgf / cm² in the flow of 105 m / sec, which means the flowis turbulen.Berbagai variation of the flow rate as well as losses of pipes, fittings , knee,experiments can be done.Keywords : PVC pipes, pumps, flow variation, Losses flow.